LEGITIMIZING THE U.S. FOREIGN POLICY TOWARDS AUTHORITARIAN REGIMES: A FRAMEWORK FOR ANALYSIS - Zukerstein, Jaroslav (European Scientific Journal, ESJ, 2014)
Although the democracy and human rights promotion are among the top priorities of the U.S. foreign policy, administrations historically have also supported various authoritarian regimes. This framework for analysis based on the theory of propaganda and speech act theory suggests that there is a possibility to deconstruct the intentions of the U.S. administrations by disclosing the propaganda elements in a discursively constructed reality. The two-layer critical discourse analysis enables scholars to discover the methods the U.S. political elites use in a neo-gramscian sense to create a public consent with a foreign policy towards authoritarian regimes.